Effect of light fasting diet therapy on lipid metabolism and sex hormone levels in patients with polycystic ovary syndrome combined with infertility - Xiaomei Jiang; Yongfeng Wang; Hong Tang; Jin Ma; Heyue Li (Gynecological Endocrinology)
Objective To investigate the effects of light fasting diet therapy, including flaxseed powder supplementation, on lipid metabolism and sex hormone levels in patients with polycystic ovary syndrome (PCOS) combined with infertility.Methods A total of 104 PCOS patients with combined infertility were divided into the control group (n = 52) and intervention group (n = 52) using a random number table method. Over a two-month study period, the control group received light fasting diet therapy with rice flour as a placebo, while the intervention group received light fasting diet therapy supplemented with flaxseed powder. Differences in general clinical data, anthropometric indicators, follicle-stimulating hormone (FSH), luteinizing hormone (LH), estradiol (E2), progesterone (P), fasting plasma glucose (FPG), fasting insulin (FINS), Homeostatic Model Assessment for Insulin Resistance (HOMA-IR), total cholesterol (TC), triglycerides (TG), high-density lipoprotein cholesterol (HDL-C) and low-density lipoprotein cholesterol (LDL-C)) were compared between the two groups.Results After treatment, both groups showed significant reductions in FSH, LH, E2, and P levels compared to baseline (p < .05). In the intervention group, the mean FINS and HOMA-IR levels were significantly lower than those in the control group following 2 months of treatment (p < .05). Furthermore, TC, TG, and LDL-C levels were significantly reduced in the intervention group compared to the control group (p < .05).Conclusion Light fasting diet therapy, especially with flaxseed powder, improves obesity, lipid, and glucose metabolism disorders in PCOS patients with infertility. However, longitudinal studies are needed to better understand these associations and assess long-term effects before considering this intervention as a standard clinical recommendation for PCOS.